2021
DOI: 10.1161/hypertensionaha.121.17336
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Aldosterone-to-Renin Ratio and Blood Pressure in Young Adults: A Longitudinal Study

Abstract: Hypertension tracks throughout childhood into adulthood. Elevated aldosterone in the setting of low renin predicts incident hypertension in normotensive adults, but the relationship is unclear in adolescents and young adults. To explore this relationship, we analyzed data from the offsprings (Gen2) of women enrolled during pregnancy into the Raine Study (population-based birth cohort), who had blood pressure (BP) measurements and blood samples at age 17 years (N=871) and age 27 years (N=758). At 17 years, fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The proportions were similar to that reported in a recent Australian prevalence study, which found that ARR values exceeded 70 pmol/mU in 25% of people newly diagnosed with hypertension (mean age, 55 years) 19 . On the other hand, only two of 758 participants in the Western Australia Raine Study (age, 27 years) had elevated ARR values using the same threshold 20 . It is unclear why the prevalence of elevated ARRs was higher among our urban ABC and TEC participants.…”
Section: Discussionsupporting
confidence: 87%
“…The proportions were similar to that reported in a recent Australian prevalence study, which found that ARR values exceeded 70 pmol/mU in 25% of people newly diagnosed with hypertension (mean age, 55 years) 19 . On the other hand, only two of 758 participants in the Western Australia Raine Study (age, 27 years) had elevated ARR values using the same threshold 20 . It is unclear why the prevalence of elevated ARRs was higher among our urban ABC and TEC participants.…”
Section: Discussionsupporting
confidence: 87%
“…Beyond the provision of normal range ARR values, the Yang et al 5 study does demonstrate the association of ARR with BP over time, under limited circumstances and with some interesting caveats. A significant association between ARR and systolic BP only was observed at 17 years of age in males but not in females.…”
mentioning
confidence: 88%
“…To that end, Yang et al 5 in this issue make a substantial contribution to the provision of normative, sex-appropriate renin, aldosterone, and ARR values for healthy young adults, filling a knowledge gap that has heretofore limited ARR as a reliable screening test for the detection of primary aldosteronism in this age group. This relatively large cohort study examined the relationship of renin, aldosterone, and ARR to BP in a primarily normotensive population of young adults from birth to 17 (871 participants) and 27 (758 participants) years of age.…”
mentioning
confidence: 99%
See 2 more Smart Citations